The development and technologizing of selected Sepedi ICT terminology - Magagane, Raesetja Linah (Rhodes University, Faculty of Humanities, School of Languages, 2011)
It is my wish that the Sepedi language speakers, through the development and technologization of certain Sepedi ICT terminology, are able to operate a computer in their own language, and implement the new developed and technologized ICT terminology (technologization). The pupils and students at their various institutions should be made comfortable in using the developed and technologized Sepedi language terminology. In the long run the Sepedi language speakers should be ensured access to the web in order to find information about Sepedi language, culture and terms in disciplines such as ICT. It is recommended in this thesis that higher learning institutions offer bursaries to students to develop all South African languages in such a manner that they can be used in all high status functions.
Keywords: Northern Sotho language -- Terms and phrases; Northern Sotho language -- Terminology; Northern Sotho language -- Computer-assisted instruction; Communication -- Technological innovations